Total factor productivity growth and technical efficiency in Indian industries - Mitra, Arup (1999)
Based on the panel data for 15 major states in India, this article estimates the time-variant technical efficiency and total factor productivity growth for 17 two-digit industry groups. The total factor productivity growth (TFPG) in a large number of industries seems to have improved across most of the states during 1985-86 to 1992-93 as compared with the rates estimated for the period 1976-77 to 1984-85. Technology acquisition, efficient utilisation of resources and infrastructure development are some of the factors which possibly contributed to the increase in TFPG. - Reproduced
Keywords: India - Industries; Industrial development